RETRACTED: Technological communication on low-intensity railway sections - Roenkov D.N.; Bogdanov D.R. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001